Experimental and Numerical Investigation of Yielding Connection in Steel Moment Frame and Infill Concrete 3D Panel - GholamReza Havaei (Iranian Society of Structrual Engineering (ISSE), 2019)
Previous studies and observations of the earthquake have shown that frame filled with concrete 3d panel wall, can have adverse effects on the seismic behavior of structures. On the other hand, yielding dampers that used with steel braces, have a high capacity to absorb and depreciating energy from the earthquake. In this paper, targets are reducing damage to the infills and moment frame in during of the earthquake, reduce the horizontal and vertical irregularities in structure. To rech these targets, Three experimentally models with half scale were constructed and tested on the shaking table under 7 scale accelerated. Also, for investigate the Effective of parameters in the seismic behavior of moment frames, using Abaqus software, finite element analysis was performed after verification of model behavior with experimentally results. Experimentally results showed that use the yielding connection between wall and frame, reduces the lateral displacement and plastic strain in the structure. Numerical analyzes showed that by adding the yielding connection to the frame and infill wall, The frame has linear behavior In high intensity earthquake, and not be created plastic hinges in the members of the frame. The input energy is amortized only in the connections. So the number and geometric specification of these connections can affect the lateral hardness and lateral strength of the structure.